2013
DOI: 10.3390/molecules18077473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Elicitors on Tanshinone Metabolic Profiling and SmCPS Expression in Salvia miltiorrhiza Hairy Root Cultures

Abstract: Tanshinones are abietane-type norditerpenoid quinone natural products found in a well-known traditional Chinese medicinal herb, Salvia miltiorrhiza Bunge. The copalyl diphosphate synthase of S. miltiorrhiza (SmCPS) is the key enzyme in the first step for transformation of geranylgeranyl diphosphate (GGPP) into miltiradiene, which has recently been identified as the precursor of tanshinones. Based on previous gene-to-metabolite network, this study examined the influences of various combined elicitors on the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…1b) (Gao et al , 2009; Cheng et al , 2013). To transform 4 into tanshinones, multiple reactions are required, including oxidation, hetero-cyclization, aromatization and de-methylation, all of which fall into the repertoire of known CYP-mediated reactions (Mizutani & Sato, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1b) (Gao et al , 2009; Cheng et al , 2013). To transform 4 into tanshinones, multiple reactions are required, including oxidation, hetero-cyclization, aromatization and de-methylation, all of which fall into the repertoire of known CYP-mediated reactions (Mizutani & Sato, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of tanshinones is initiated by cyclization of (E, E,E)-geranylgeranyl diphosphate (GGPP), the general diterpenoid precursor, to the abietane miltiradiene (hereafter '4'), which is mediated by two enzymes, SmCPS1 and SmKSL1 ( Fig. 1b) (Gao et al, 2009;Cheng et al, 2013). To transform 4 into tanshinones, multiple reactions are required, including oxidation, heterocyclization, aromatization and demethylation, all of which fall into the repertoire of known CYP-mediated reactions (Mizutani & Sato, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The first reaction, catalyzed by copalyl diphosphate synthase (EC 5.5.1.12), is based on carbon-carbon double-bond protonation that leads to the production of copalyl diphosphate (CPS). Subsequent cyclization and rearrangement reactions, catalyzed by kaurene-like synthase (KLS), result in the formation of a miltiradiene moiety, a key intermediate in tanshinone biosynthesis [3,4]. Both CPS and KSL enzymes were previously cloned in S. miltiorrhiza.…”
Section: Introductionmentioning
confidence: 99%
“…Yeast extract is a natural source of cytokinins, vitamins, enzymes, minerals, nucleic acids and carbohydrates, and has stimulatory effects on plants during the vegetative and reproductive growth stages . Additionally, it has been demonstrated that yeast cell wall ingredients, such as polysaccharide fraction, can act as elicitors in plant signal transduction pathways as a plant defense response, so it is not only active yeast extract that may be used in agricultural applications . Yeast extract is one of the most common natural elicitors used for the enhancement of secondary metabolites in in vitro plant cultures .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Yeast extract is one of the most common natural elicitors used for the enhancement of secondary metabolites in in vitro plant cultures. 4,6 Because of their natural origin, these extracts are environmentally friendly products which can be used in agricultural applications for stimulating the plant defense mechanism and improving the nutraceutical quality of some edible plants. There are reports concerning the influence of yeast extract application on the yield and resistance of some vegetables, 5,8 but studies have not been done on the effect of elicitation with yeast on the content and activity of phytochemicals in leafy vegetables.…”
Section: Introductionmentioning
confidence: 99%